Simple waveguide model of arbitrary filled plane-plane cavity - Anokhov, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Some waveguide features responsible for angular structure of a plane-plane cavity output emission, which were not discussed before, are considered. A number of common regularities in mode structure of such cavity at the level of their elementary organization is established. Among them are: the angular quantization of initial plane waves spectrum, the real size of diffraction losses, the phenomenon of reorientation of plane waves in waveguide propagation, the role of optical filling of the cavity, etc. The obtained data most essentially supplement the traditional representations of mode properties in the area of the small cavity apertures characterized by the Fresnel number about or less than unity.